Social police and the mechanisms of prevention. Patrick Colquhoun and the condition of poverty - Neocleous, Mark (The British journal of criminology, 2000)
This article reassesses the work of Patrick Colquhoun by reconsidering his notion of prevention. It argues that Colquhoun has been badly served by having his notion of prevention understood in the light of the emergence of the new police in 1829. This has obscured the importance of poverty, indigence and political economy to Colquhoun's understanding of police. I suggest that Colquhoun's work should be of interest as much to the discipline of social policy as police studies, and use this argument as a springboard into a wider argument concerning the historical, political, and conceptual links between police and social policy as mechanisms for the fashioning of the market. The major suggestion is that the concept of a social police' may be a useful way to understand these links